2017
DOI: 10.1111/ejn.13620
|View full text |Cite
|
Sign up to set email alerts
|

Reduced reward‐related neural response to mimicry in individuals with autism

Abstract: Mimicry is a facilitator of social bonds in humans, from infancy. This facilitation is made possible through changing the reward value of social stimuli; for example, we like and affiliate more with people who mimic us. Autism spectrum disorders (ASD) are marked by difficulties in forming social bonds. In this study, we investigate whether the reward-related neural response to being mimicked is altered in individuals with ASD, using a simple conditioning paradigm. Multiple studies in humans and nonhuman primat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Research on healthy adults reveals that one aspect of automatic facial mimicry is the (unconscious) desire to affiliate with the target (Lakin & Chartrand, 2003; Stel & Vonk, 2010). Meanwhile, previous research on individuals with ASD and high ASD traits indicate atypical sensitivity to the social rewards of mimicking and being mimicked by strangers (Hsu, Neufeld, & Charkrabati, 2018; Sims et al, 2012). Although a core symptom of the disorder is reduced affiliation with others, children with ASD tend to have typical attachment rates to their parents (Capps, Sigman, & Mundy, 1994; Rutgers, Bakermans-Kranenburg, van Ijzendoorn, & Van Berckelaer-Onnes, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Research on healthy adults reveals that one aspect of automatic facial mimicry is the (unconscious) desire to affiliate with the target (Lakin & Chartrand, 2003; Stel & Vonk, 2010). Meanwhile, previous research on individuals with ASD and high ASD traits indicate atypical sensitivity to the social rewards of mimicking and being mimicked by strangers (Hsu, Neufeld, & Charkrabati, 2018; Sims et al, 2012). Although a core symptom of the disorder is reduced affiliation with others, children with ASD tend to have typical attachment rates to their parents (Capps, Sigman, & Mundy, 1994; Rutgers, Bakermans-Kranenburg, van Ijzendoorn, & Van Berckelaer-Onnes, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that faces that consistently mimic the participant are liked more and looked at longer compared to faces that consistently perform the facial expression opposite to that of the participant (44). In another study in our lab, we used the same mimicry conditioning to demonstrate that mimicking as compared to anti-mimicking faces evoked stronger reward-related activation of the ventral striatum in NT but not ASD participants (53). Together with these previous findings, the current study contributes to the evidence for a weakened link between reward and mimicry people with in ASD in both directions.…”
Section: Discussionmentioning
confidence: 99%
“…During both parts of the experiment, stimuli were presented using E-Prime 2.0 (Psychology Software Tools, PA, USA). Participants took part in a different experiment reported elsewhere (53) before they were debriefed and dismissed.…”
Section: Methodsmentioning
confidence: 99%
“…A further possible mechanism involves the reward processing system. Thus, human and macaque studies have shown that being mirrored leads to greater reward-related responses, including self-reported liking, preferential gaze, and ventral striatal activity [5254]. Accordingly, maternal mirroring is likely to reinforce infant communicative gestures through eliciting such reward-related activity, leading to their increase.…”
Section: Discussionmentioning
confidence: 99%